2019
DOI: 10.1186/s13014-019-1374-1
|View full text |Cite
|
Sign up to set email alerts
|

Dose-volume analysis of predictors for acute anal toxicity after radiotherapy in prostate cancer patients

Abstract: Background This study aimed to evaluate the clinical and dosimetric factors predictive of acute anal toxicity (AAT) after radiotherapy in prostate cancer (PCa) patients with or without hemorrhoids. Methods We analyzed data from 347 PCa patients (248 cases treated from July 2013 to November 2017 for training cohort and 99 cases treated in 2018 for validation cohort) treated with pelvic radiotherapy at a single institution. Anal canal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The symptoms of acute proctitis are diarrhea and tenesmus and those of chronic proctitis are bleeding and painful defecation (10). However, if hemorrhoids are exacerbated, bleeding and pain appear early in the RT period (5,6). Therefore, the differential diagnosis of hemorrhoid aggravation and radiation-induced proctitis is essential to ensure that proper treatment choices are made, and it should be determined whether acute anal symptoms are due to hemorrhoid aggravation or lower rectal wall problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The symptoms of acute proctitis are diarrhea and tenesmus and those of chronic proctitis are bleeding and painful defecation (10). However, if hemorrhoids are exacerbated, bleeding and pain appear early in the RT period (5,6). Therefore, the differential diagnosis of hemorrhoid aggravation and radiation-induced proctitis is essential to ensure that proper treatment choices are made, and it should be determined whether acute anal symptoms are due to hemorrhoid aggravation or lower rectal wall problems.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation proctitis is a typical side-effect associated with pelvic RT (3,4). In particular, in patients with hemorrhoids, RT may aggravate anal symptoms such as pain or bleeding (5,6). In general, radiation proctitis tolerance is around 50 Gy (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the dosevolume effect, radiotherapy-induced injury can be assessed by radiation dose and/or volume calculations. In this way, rectal toxicity (30,31), acute gastrointestinal toxicity (32,33), anal toxicity, and salivary gland injury were reported (34)(35)(36)(37)(38)(39)(40)(41)(42)(43) and precisely predicted (44). Conversely, Kim et al found that a higher dose was not associated with cervical esophageal cancer radiotherapy-induced stenosis (45).…”
Section: B) Dose-volume Effectmentioning
confidence: 99%
“…Currently, radiotherapy and ADT are combined by starting radiotherapy 2–3 months after ADT (it can be extended appropriately for patients with large prostate volume) to reduce the prostate volume, stabilize its size, and reduce radiation damage to the surrounding organs 39,40 …”
Section: Medicationsmentioning
confidence: 99%